Filtering of the noise generated by shaft neck contour deformations in monitoring systems - Batko, Wojciech; Banek, Tadeusz (Zielona Góra: Uniwersytet Zielonogórski)
The paper presents an applicable, approximate solution to the filtering-prediction problem for the diagnostic signals. It takes into consideration the possibility of compensating the noise generated by the deformations of the surface geometry of a shaft neck. The equations of the Kalman-Bucy model were the basis for the calculations of the structure of the filter-predictor under investigation.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka